Divergent germination strategies of Phragmites australis seeds for tidal flat gradient adaptation and the implications for coastal wetland restoration - Jia, Peng; Li, Dezhi; Yu, Caifen; Jia, Jing; Wang, Jiangtao; Wang, Ying; Chen, Jing (Frontiers in Plant Science, 2025)
Phragmites australis, capable of both sexual and asexual reproduction, widely distribute along the tidal flat gradient in the Chongming Dongtan wetlands, eastern China. This study investigates whether P. australis exhibits maternal effects by examining how seed germination strategies are influenced by habitat origin, soil properties, storage temperature, and salinity conditions. Seeds were collected from different tidal flat habitats, and their germination responses were tested under varying salinity levels (0–2.0%), storage temperatures (4 °C and room temperature), and soil conditions. Germination rates, speeds, index and potentials were measured, and structural equation modeling (SEM) was used to analyze the effects of environmental factors. These results showed that when the salinity was up to 1.5%, the seed germination rate was 1.3% to 7.7%. When treated with a salinity level of 2.0%, the seed germination rates of different tidal flat populations decreased by 94.3% (L), 96.5% (IN), 100% (M) and 99.2% (H), respectively, compared to the control group. With the increase in salinity, the germination speeds of different tidal flats slowed down, and the germination index decreased. 4°C storage significantly enhanced the seed germination rate and germination potential of the low-tidal flat population (L) relative to room-temperature storage. Soil salinity and water content were major factors influenced germination rates after storing seeds at 4°C. However, germination rates and potentials were positively correlated with the soil phosphorus. Meanwhile, the seed germination indexes and speeds were more significantly affected by the room temperature. The SEM model explained 74% and 50% of the seed germination parameters under the seed storage condition at 4°C and room temperature, respectively. And the tide level of its directly decreasing effect for the seed germination parameters was higher at 4°C with -0.97 than at room temperature with -0.16. The results indicated that after ripening (low-temperature seed storage) differentially promoted the P. australis seed germination collected from the tidal flat gradient in a subtropical marine monsoon climate salt marsh and demonstrated maternal effect adaptation. Consequently, using seeds of P. australis along the tidal flat gradient to restore the original population could be considered an effective and economical method.